Estruturação da cidade de Campina Grande: as estratégias e intencionalidade do mercado imobiliário - Costa, Leonardo Barboza da (2013)
The aim of the dissertation is to analyse the process of structuring in Campina Grande - PB, from the actions and intentions of the real estate market. For such study we consider the role of the State in urban improvements in aspects related to infrastructure (piped water and sewage and garbage collection), with population density, income levels and literacy of household heads as being important aspects in the real estate market valorization and which attract other modernizer ventures such as supermarkets, shopping centers, horizontal and vertical closed condominiums. The locations of these large projects in the city influence the action of the real estate market at times taking advantage of a previous valorization process, at times taking part in the process. Therefore, we assume that these new ways of living and consuming in the city add a differential value to a particular location. These elements help us to understand the action of the real state market and the valorization process of the city. We highlight the following resources to help us to analyse this process the map of environmental inclusion / exclusion, and ITBI guidebooks (property tax) for the years 1995, 2000, 2005, and 2010. The resource of the inclusion / exclusion map assists in the comprehension of the areas of best quality built environment. And the ITBI guides enable us to determine the prices of the different properties analysed in this research and how the real estate market strategies take into consideration these prices on its operations in the city. These data are presented as a way to get a real sense of how the prices have been increasing in some areas of the city, considering in this aspect the variation of price indices through the use of "citizen calculator" provided by the Central Bank, which allows a real comparison of this valorization process between the years 1995-2010 analysed. It is thus established a distinction between the value derived from work incorporated into urban space and monetary price charged for a specific venture and specific location. In the process of structuring the city we better understand the arrangement of layers incomes in the city over the years, as well as the reasons for the location of modernizers venture projects, with the mediation of the real estate market agents in the city.